Association of Self-Compassion With Suicidal Thoughts and Behaviors and Non-suicidal Self Injury: A Meta-Analysis - Suh, Hanna; Jeong, Jisun (Frontiers in Psychology, 2021)
Objectives: Self-compassion functions as a psychological buffer in the face of negative life experiences. Considering that Suicidal Thoughts and Behaviors (STBs) and Non-Suicidal Self-Injury (NSSI) are often accompanied by intense negative feelings about the self (e.g., self-loathing, self-isolation), self-compassion may have the potential to alleviate these negative attitudes and feelings towards oneself. This meta-analysis investigated the associations of self-compassion with STBs and NSSI. Methods: A literature search finalized in August 2020 identified 18 eligible studies (13 STBs effect sizes and 7 NSSI effect sizes), including 8,058 participants. Two studies were longitudinal studies, and the remainder were cross-sectional studies. A random-effects meta-analysis was conducted using CMA 3.0. Subgroup analyses, meta-regression, publication bias analyses were conducted to probe potential sources of heterogeneity. Results: With regards to STBs, a moderate effect size was found for self-compassion (r = - .34, k = 13). Positively worded subscales exhibited statistically significant effect sizes: self-kindness (r = -.21, k = 4), common humanity (r = -.20, k = 4), and mindfulness (r = -.15, k = 4). For NSSI, a small effect size was found for self-compassion (r = -.29, k = 7). There was a large heterogeneity (I2 = 80.92% for STBs, I2 = 86.25% for NSSI), and publication bias was minimal. Subgroup analysis results showed that sample characteristic was a moderator, such that a larger effect size was witnessed in clinical patients than sexually/racially marginalized individuals, college students, and healthy-functioning community adolescents. Conclusions: Self-compassion was negatively associated with STBs and NSSI, and the effect size of self-compassion was larger for STBs than NSSI. More evidence is necessary to gauge a clinically significant protective role that self-compassion may play by soliciting results from future longitudinal studies or intervention studies.